2002
DOI: 10.1128/jb.184.14.3765-3773.2002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis and Regulation of the Divergent spuABCDEFGH-spuI Operons for Polyamine Uptake and Utilization in Pseudomonas aeruginosa PAO1

Abstract: A multiple-gene locus for polyamine uptake and utilization was discovered in Pseudomonas aeruginosa PAO1. This locus contained nine genes designated spuABCDEFGHI (spu for spermidine and putrescine utilization). The physiological functions of the spu genes in utilization of two polyamines (putrescine and spermidine) were analyzed by using Tn5 transposon-mediated spu knockout mutants. Growth and uptake experiments support that the spuDEFGH genes specify components of a major ABC-type transport system for spermid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 33 publications
8
111
0
Order By: Relevance
“…Besides PauB enzymes, genetic analysis from our previous studies (7,16) supported participation of a putative putrescine:pyruvate transaminase SpuC in PUT catabolism. As shown in Table 2, while PAO5008 with a lesion on spuC was partially defective in growth on PUT or CAD as the sole source of carbon or nitrogen in the liquid medium, growth on these two diamines was completely abolished in PAO5730 devoid of spuC and all four pauB genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides PauB enzymes, genetic analysis from our previous studies (7,16) supported participation of a putative putrescine:pyruvate transaminase SpuC in PUT catabolism. As shown in Table 2, while PAO5008 with a lesion on spuC was partially defective in growth on PUT or CAD as the sole source of carbon or nitrogen in the liquid medium, growth on these two diamines was completely abolished in PAO5730 devoid of spuC and all four pauB genes.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids pGU101 and pGU102 were used to measure pauA2 and pauA1 promoter activities, respectively (7,16). Regulatory regions of pauA4 (PA2040) and pauA5 (PA3356) were amplified by PCR from the genomic DNA of P. aeruginosa PAO1 using the following primers: PpauA5F (5=-GGT GGA TCC GAG AAT CAA CGG CAG TAC TC-3=), PpauA5R (5=-GGT AAG CTT GAT GCA TTG CAG CAG CAC GCCA-3=), PpauA4F (5=-GGT GGA TCC TTG AAC GAT CTT GCT CTT CGT ATC-3=), and PpauA4R (5=-GGT AAG CTT GAA GGA ACA GGC TCG GCT CAG-3=).…”
Section: Methodsmentioning
confidence: 99%
“…Polyamines (including putrescine and spermidine) are a group of ubiquitous polycations necessary for cell growth (Lu et al, 2002). In P. aeruginosa, putrescine can be synthesized from arginine through the arginine decarboxylase pathway (Patel et al, 2006).…”
Section: Upregulation Of N Assimilationmentioning
confidence: 99%
“…For the ADC pathway, although the presence of arginine-inducible ADC activity in the conversion of arginine into agmatine has been reported in an early study (29), the corresponding gene has not been identified. Recent studies in this laboratory have reported the characterization of the aguBA and spuC genes, which encode enzymes for the conversion of agmatine into 4-aminobutyrate of the ADC pathway (26,34). Exogenous agmatine but not arginine induced these genes (14,29).…”
mentioning
confidence: 99%